Immunogenicity study of dna vaccine and dna vaccine carrier expressing vp1 of enterovirus 71 in the prime boost vaccination strategy - Nur Ayuni, Kadir (2008)
Enterovirus 71 {EV71) is a highly infectious causative agent of hand, foot and mouth disease {HFMD) in children and which could lead to severe neurological complications. In Malaysia, the first epidemic occurred in 1997 in Sarawak and caused 34 deaths due to severe neurological syndrome. There is currently no vaccine available against EV71. Vaccination is considered the most effective means to control EV71 infection. Thus our group have exploring the development of a candidate vaccine involving the construction of a synthetic VP1 gene of EV71 fused to a ubiquitin (UbGR) gene and cloned into a DNA vaccine vector with a strong eukaryotic promoter known as pVAX1, to create the candidate DNA vaccine pVaxUbVP1. The immunogenicity of the constructed DNA vaccine was evaluated in BALC/c mice involving two methods of delivery: as a naked DNA vaccine delivered intramuscularly or delivered orally via the live attenuated bacteria Salmonella typhi Ty21 a, of which the recombinant strain carrying pVaxUbVP1 was designated as StUbVP1. Both candidate vaccines were used in homologous and heterologous prime boost approaches: Formats A (pVaxUbVP1 alone), B ( StUbVP1 alone), C (StUbVP1 as primer vaccine and pVaxUbVP1 as booster), and D (pVaxUbVP1 as primer vaccine and StUbVP1 as booster). The results indicated that total lgG levels in serum was significant in Formats A and D whereas lgG subclasses assay showed that lgG2a levels were higher than lgG1 levels in both immunization formats. Production of in vitro IFN-y was significant in mice vaccinated using Formats A, B and D, whereas IL-4 production was relatively low in all groups of immunization but shows a significant increase in Format D. The percentage of intracellular cytokine {IFN-y, IL-2 and IL-4) production by CD4+ and cos• population of T cells showed a moderate to high response in Formats A and D. The analyses also showed that the use of pVaxUbVP1 in a homologous prime boost format (Format A) resulted in a Th1 type of immune response whereas using Format D (pVaxUbVP1 as primer vaccine and StUbVP1 as booster) gave a mixed Th1-Th2 types immune response. In conclusion, pVaxUbVP1 used alone in a homologous prime boost approach or as the primer vaccine in a heterologous prime boost immunization format together with StubVP1, show potential for further development as a vaccine against EV71.